Adsorption and dispersion capability of polycarboxylate-based superplasticizers: a review. Issue 5 (3rd September 2022) - Ma, Yihan; Sha, Shengnan; Zhou, Beibei; Lei, Fengzhen; Liu, Yi; Xiao, Yuchong; Shi, Caijun
Abstract : Adsorption of polycarboxylate ester/ether (PCE) superplasticizer on the cementitious materials and steric effect of its side chain determine to its dispersion and water-reducing capability. This paper reviews the effect of molecular structure of PCE and characteristics of cementitious system on its adsorption behavior, and build up the relationship between adsorption of PCE and its dispersion performance. The role of adsorbed and non-adsorbed PCE on its dispersion properties in different water-to-binder ratio system are discussed and analyzed. The adsorption amount of PCE increases with its increased carboxylate density and length of main chain as well as molecular mass, while its steric repulsion depends on the side chain length that affects the adsorption conformation in a large degree. In a constant water-to-binder ratio system, more adsorbed PCE is beneficial to the enhancement of dispersion capability paste. Apart from that adsorbed PCE, the non-adsorbed PCE with appropriate molecular mass also plays a lubrication and favors to the decrease of frictions between particles, resulting in the improvement of workability of paste at a low water-to-binder ratio. This article can provide a better understanding on the adsorbed behaviors of PCE and a theoretical basis on the improvement of dispersion capability of PCE and the design of PCE used for low water-to-binder system.